2008
DOI: 10.1007/s12253-008-9094-0
|View full text |Cite
|
Sign up to set email alerts
|

INCENP (Inner Centromere Protein) is Overexpressed in High Grade Non-Hodgkin B-cell Lymphomas

Abstract: Inner centromere protein (INCENP) is a member of the Chromosomal Passenger Complex (CPC), which is a four member protein complex essential for proper completion of mitosis and cell division (cytokinesis). Inappropriate chromosomal segregation and cytokinesis due to deregulated expression of chromosome passenger proteins may lead to aneuploidy and cancer including lymphomas. According to our knowledge this is the first study investigating immunohistochemical expression of INCENP in lymphoma cases and cancer tis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…High INCENP expression has been reported in some cancer types. In high-grade non-Hodgkin B-cell lymphomas (18), there is significantly higher nuclear IHC signal of INCENP compared with low-grade ones. High expression of three components of CPC (Aurora B, INCENP, and survivin) except Borealin is associated with poor survival rate in patients with NSCLC (19).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…High INCENP expression has been reported in some cancer types. In high-grade non-Hodgkin B-cell lymphomas (18), there is significantly higher nuclear IHC signal of INCENP compared with low-grade ones. High expression of three components of CPC (Aurora B, INCENP, and survivin) except Borealin is associated with poor survival rate in patients with NSCLC (19).…”
Section: Discussionmentioning
confidence: 91%
“…(GWAS) studies have identified SNPs in INCENP that are linked to increased susceptibility and risk in breast, ovarian, and prostate cancer (16,17). In addition, INCENP has been found to be overexpressed in high-grade non-Hodgkin B-cell lymphomas and non-small-cell lung cancer, and proposed to be a biomarker for poor prognosis in these types of cancer (18,19). However, the function and therapeutic potential of targeting INCENP in neuroblastoma remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, CENP-A has been associated with cancers such as breast cancer and lung adenocarcinoma (33,34). At the same time, CENP-E, CENP-F, and inner centromere protein have been demonstrated to contribute to carcinogenesis (35)(36)(37)(38). All observations suggest that deregulation of centromere proteins is common in the development and progression of various tumors.…”
Section: Discussionmentioning
confidence: 99%
“…INCENP is a versatile domain protein composed of two types of peptides (135 and 155 kD) in close contact with chromosome proteins during cell division. INCENP , a part of a protein complex known as the chromosomal passenger complex (CPC), does not only play an important role in cell division [ 16 ] but is also closely related to cancer [ 17 , 18 ] and reproductive disorders [ 19 ]. Hering et al (2014) performed a genome-wide association study of high and low sperm motility of Holstein cattle to identify candidate genes associated with semen quality by screening all the genetic distances that significantly mark 1 Mb.…”
Section: Introductionmentioning
confidence: 99%